Crystalline forms of darolamide

The nanocrystalline form of darolutamide addresses solubility and bioavailability issues by enhancing surface area and solubility, thereby reducing daily doses and side effects.

CN118974018A9Pending Publication Date: 2024-12-24QUIMICA SINTETICA SA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380023718.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-02-28
Filing Date
2023-02-27
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

Existing crystalline forms of darolutamide, such as Form I, suffer from poor solubility and bioavailability, leading to high doses required for therapeutic efficacy, which in turn cause significant side effects in patients due to its classification as a Class II drug in the Biopharmaceutical Classification System (BCS).

Method used

Development of a nanocrystalline form (NC form) of darolutamide with a specific surface area of 40-150 m^2/g, characterized by broad X-ray diffraction peaks, which enhances solubility and bioavailability through a method involving controlled crystallization using organic solvents and antisolvents.

Benefits of technology

The NC form exhibits eight times higher solubility in physiological conditions compared to traditional forms, reducing the daily dose needed and minimizing adverse reactions, while maintaining chemical and physical stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118974018A9_ABST
    Figure CN118974018A9_ABST
Patent Text Reader

Abstract

The present invention relates to a crystal form of darolutamide and a preparation method thereof. In addition, the present invention also relates to the use of the crystal form in preparing a pharmaceutical composition for treating prostate cancer. #imgabs0#
Need to check novelty before this filing date? Find Prior Art

Description

Field of the Invention

[0001] The present invention relates to a new crystalline form of darolutamide, referred to herein as NC form, and a method for preparing the same. In addition, the present invention also relates to a pharmaceutical composition comprising the new crystalline form and one or more acceptable excipients. Background Art

[0002] Daroltamide, chemically known as N-[(2S)-1-[3-(3-chloro-4-cyanophenyl)-1H-pyrazol-1-yl]-propan-2-yl]-5-(1-hydroxyethyl)-1H-pyrazole-3-carboxamide, is a drug approved by regulatory agencies in the United States, the European Union, and Australia for the treatment of non-metastatic castration-resistant prostate cancer (CRPC). The active pharmaceutical ingredient present in

[0003] Its chemical structure is shown in formula (I).

[0004]

[0005] The structure shown in formula (I) refers to N-[(2S)-1-[3-(3-chloro-4-cyanophenyl)-1H-pyrazol-1-yl]-propan-2-yl]-5-(1-hydroxyethyl)-1H-pyrazole-3-carboxamide and its tautomers, namely N-[(2S)-1-[3-(3-chloro-4-cyanophenyl)-1H-pyrazol-1-yl]-propan-2-yl]-3-(1-hydroxyethyl)-1H-pyrazole-5-carboxamide. As those skilled in the art will recognize, this is because the hydrogen atoms of the pyrazole ring can exist in tautomeric equilibrium between the 1-position and the 2-position.

[0006] Darolutamide comprises a mixture of two pharmacologically active diastereoisomers in a molar ratio of 1:1, and the chemical structures are shown in formulas (Ia) and (Ib):

[0007]

[0008]

[0009] These two diastereoisomers are mutually converted into ketodarolutamide in vivo, which is the main pharmacologically active metabolite of darotamide, and its chemical structure is shown in formula (II), namely 3-acetyl-N-[(2S)-1-[3-(3-chloro-4-cyanophenyl)pyrazol-1-yl]propan-2-yl]-1H-pyrazole-5-carboxamide.

[0010]

[0011] Darolutamide and its preparation method were first disclosed in WO2011 / 051540 filed by Bayer AG.

[0012] Bayer's WO2016 / 120530 discloses Form I, i.e., the form used to prepare the final drug, such as Fig.11 shown.

[0013] In addition, the patent application also describes Form I' and Form I", which are polymorphs referring to diastereomers of Formula Ia and Formula Ib, respectively. As mentioned above, these polymorphs are not useful for obtaining the final drug because the darolutamide drug contains a 1:1 mixture of each diastereomer.

[0014] Bayer's WO2018 / 162793 discloses crystalline particles of darolamide, which have good properties in the subsequent formulation process: the specific surface area (SSA) of the particles is 8m 2 / g to 16m 2 / g (measured by BET), preferably 10m 2 / g to 15m 2 / g, and are round in shape. In WO2018 / 162793, the polymorph of the round crystalline particles has not been fully characterized: the patent application discloses that they are at least partially in form I. In addition, in WO2018 / 162793, the applicant discloses that the powder consisting of darolamide in form I obtained according to the teaching of WO2016 / 120530 is composed of heterogeneous particles with undefined morphology, which means that it is challenging to formulate the polymorph of darolamide. Specifically, in the examples provided during the examination of EP3592732, it is shown that the SSA of the crystalline particles of Example 1 of WO2016 / 120530 is 22.1 m 2 / g.

[0015] Document EP3495352A1 discloses Form I darolamide before and after grinding. Grinding is a common method to reduce particle size, and thus generally increase specific surface area, to improve dissolution rate and bioavailability of the compound. In Example 13 of EP3495352A1, the applicant shows that the crystallinity of Form I prepared according to WO2016 / 120530 is significantly reduced after grinding, such as Fig.12 This is supported by the XRPD pattern shown, which shows the same peaks as Form I, but with much lower intensity, and also the presumed presence of amorphous material.

[0016] Daroltamide is formulated as a 300 mg film-coated immediate-release tablet for oral administration: the dose is 600 mg (2 tablets of 300 mg), twice daily, taken with food, equivalent to a total daily dose of 1200 mg. Since daroltamide is classified as a Class II drug in the Biopharmaceutical Classification System (BCS), which is a poorly soluble drug in the physiological pH range, the high dose is required to achieve therapeutic plasma concentrations after oral administration. The higher the dose of the active ingredient, the greater the side effects on the patient.

[0017] Therefore, it is clear that in order to reduce the daily dose, it would be desirable to have new crystalline forms of darolutamide with improved chemical and physical properties. This would require reducing the burden of tablets and side effects on patients, thereby improving the therapeutic effect. SUMMARY OF THE INVENTION

[0019] Therefore, a main aspect of the present invention is to provide a new crystalline form of darolutamide, referred to herein as Form NC, which has improved properties such as good chemical and physical stability, high solubility, enhanced bioavailability and good processability.

[0020] Another aspect of the present invention is to provide a method for preparing the above-mentioned new crystalline form of darolutamide.

[0021] Yet another aspect of the present invention is the use of the novel darolutamide to prepare a formulation.

[0022] Another aspect of the present invention is to provide a tablet, preferably a film-coated tablet, comprising the novel darolutamide and at least one pharmaceutically acceptable excipient.

[0023] BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The X-ray powder diffraction pattern (XRPD) of NC Form darolutamide is shown.

[0025] Figure 2 An exemplary differential scanning calorimetry (DSC) curve of darolamide Form NC is shown (30°C to 250°C; 10°C / min).

[0026] Figure 3 The NC type darolamide is shown 13 C CPMAS NMR spectroscopy.

[0027] Figure 4 The infrared spectrum (IR) of NC Form darolutamide is shown.

[0028] Figure 5 A scanning electron microscope (SEM) image of NC-form darolutamide is shown. (Magnification: x20000, scale bar: 1 micron).

[0029] Figure 6 The calibration curve for SSA measurement is shown.

[0030] Figure 7 The calibration curve for the solubility determination of darolutamide samples is shown.

[0031] Figure 8 Two time dependent solubility curves of NC darolutamide relative to Form I and round crystalline particles measured at pH 1 and 7.5 at 37° C. are shown. The x-axis represents time (minutes) and the y-axis represents the concentration of darolutamide in solution (mg / mL).

[0032] Fig. 9 An example of a spectral fitting (PF) plot is shown which employs the term "split pseudo-Voigt" to describe the slightly asymmetric peak shape associated with the peaks of NC-form darolutamide near about 8.6 and 10.4 degrees 2θ.

[0033] Fig.10 Shown is an overlay of X-ray powder diffraction patterns (XRPD) of darolutamide Form NC obtained at time zero and 1 month, 3 months, 6 months and 12 months during a stability study at 40°C and 75% RH as described in Example 20.

[0034] Fig.11 The results show that type I darolamide and XRPD of 300 mg.

[0035] Fig.12 An overlay of the XRPD traces of Form I and Form NC taken from EP3495352A1 before and after milling is shown.

[0036] Fig.13 An overlay of the XRPD traces of the Type I sample and its two ground samples obtained from Comparative Example 1a (Type I obtained according to WO2016 / 120530), Comparative Example 1b and Comparative Example 1c (hand-ground and ground in a grinding device according to EP3495352A1, respectively) are shown. DETAILED DESCRIPTION OF THE INVENTION

[0038] Unless otherwise specified, all terms used in this application should be understood as having ordinary meanings known in the art.

[0039] “Nanocrystalline form of N-[(2S)-1-[3-(3-chloro-4-cyanophenyl)-1H-pyrazol-1-yl]-propan-2-yl]-5-(1-hydroxyethyl)-1H-pyrazole-3-carboxamide” or “nanocrystalline form of darolamide” or “nanocrystalline form” or “nanocrystalline darolamide” or “NC form” or “NC crystal form” are used interchangeably herein and refer to a solid crystalline form of darolamide, wherein each particle of the crystalline form is composed of crystallites having a size of less than 100 nm.

[0040] Nanocrystalline materials are defined in the art as, for example: ultrafine grained single-phase or multi-phase polycrystals with a grain size of 1 nm to 100 nm (B. Movahedi, "Introductory Chapter: Nanocrystalline Materials", Nanocrystalline Materials, Feb. 2020, doi: 10.5772 / intechopen.90255); single-phase or multi-phase polycrystalline solids with a crystallite size of only a few nanometers, usually less than 100 nm (Nasrollahzadeh, M. et al., "Chapter 2-Types of Nanostructures" Interface Science and Technology, Volume 28, 2019, Pages 29-80); or polycrystalline materials with a grain size of up to about 100 nm (Suryanarayana, C., "Nanocrystalline Materials", International Materials Reviews, 1995, 40 (2): 41-64).

[0041] The term "crystal" or "grain" as used herein refers to the coherent scattering area constituting each darolamide particle. The crystallite size can be estimated by using an X-ray diffraction pattern (XRPD). The peak width of the XRPD pattern is related to the crystallite size, which changes inversely with the crystallite size: the peak broadens as the crystallite size decreases. This broadening can be associated with the crystallite scale using the Scherrer equation, which is generally applicable to submicron-sized materials, see, for example, U. Holtzward and N. Gibson's 'The Scherrer equation versus the'Debye-Scherrer equation', Nature Nanotechnology, 2011, 6, 534.

[0042] Visible size estimates by scanning electron microscopy (SEM) or transmission electron microscopy (TEM) differ from X-ray-based estimates because the microscopy technique images the aggregates and establishes an average from a number-based distribution, whereas X-ray methods detect mass-based averages.

[0043] As used herein, the term "broad peaks" refers to a typical XRPD pattern of a nanocrystalline form characterized by broad peaks, far exceeding the width determined essentially by instrumental effects.

[0044] The terms "crystalline Form I of darolutamide" or "Form I darolutamide" or "Form I" are used interchangeably herein and refer to the crystalline form of darolutamide that has been disclosed in WO2016 / 120530 and is referred to as Form I. As reported in the WO2016 / 120530 patent application, Form I darolutamide may be characterized in that, at room temperature, the crystalline form of When measured with Cu-Kα radiation, the powder X-ray diffraction pattern includes reflections at 2θ of 8.5±0.15 degrees, 10.4±0.15 degrees, 16.6±0.15 degrees, 16.9±0.15 degrees and 24.3±0.15 degrees.

[0045] As used herein, the term "round crystalline particles" of darolutamide refers to particles having a specific surface area (SSA) of 8 m 2 / g to 16m 2 / g, preferably 10m 2 / g to 15m 2 / g of darolutamide, and / or round darolutamide crystalline particles having a large volume median diameter of 100 μm to 1000 μm, preferably 120 μm to 800 μm, more preferably 150 μm to 750 μm, the specific surface area being measured by a three-point nitrogen adsorption technique based on Brunauer, Emmett and Teller (BET) theory, and the volume median diameter being measured by laser light diffraction using an air dispersion medium and applying the Fraunhofer optical model, which is obtained in accordance with the teachings of WO2018 / 162793.

[0046] The term "about" refers to a range that includes experimental error, typically the error that occurs when making measurements, such as ±5% or ±2% or ±1%. Sometimes, such a range can be within experimental error, typically within the experimental error of a standard method for measuring and / or determining a given value or range. Specifically, for the measurement uncertainty of a multi-point BET specific surface area parameter, if the SSA value is greater than 2 m 2 / g, the uncertainty is equal to 15%. If the SSA value is less than 2m 2 / g, the uncertainty is 20%. It is expressed as an expanded uncertainty obtained by multiplying the standard uncertainty by a coverage factor k equal to 2, corresponding to a confidence level of approximately 95%. The uncertainty is related to the analytical method and is a percentage value obtained after analyzing a representative group of samples within the measuring range of the instrument.

[0047] As used herein, the term "room temperature" refers to a temperature of about 18°C ​​to about 25°C.

[0048] The term "C5 to C7 straight or branched chain alkane" includes pentane, hexane and heptane having a straight or branched chain structure.

[0049] As used herein, the term "substituted cycloalkane" refers to cyclopentane and cyclohexane having one or more than one alkyl substituent.

[0050] As used herein, the term "antisolvent" refers to a liquid that reduces the solubility of darolutamide in a solvent.

[0051] The term "any solid form" as used herein refers to any crystalline or amorphous form of darolutamide.

[0052] The term "amorphous" refers to a solid form of a non-crystalline compound. Amorphous compounds have no long-range order and do not display a well-defined X-ray diffraction pattern with reflections.

[0053] The term "excipient" refers to any substance contained in the final pharmaceutical dosage form, in addition to the active ingredient, which may not generally have a therapeutic effect in itself. Excipients are essential for the administration of active substances because they allow the drug to be delivered to the target site. Excipients generally refer to the raw materials that go into the composition of a pharmaceutical preparation, and their purpose is, for example, to give shape, facilitate administration and retain the active ingredient. In addition, excipients help to give the pharmaceutical preparation characteristics from the perspective of appearance, stability, biopharmaceutical properties and patient acceptance. Disintegrants, lubricants, fillers, binders, flavoring agents and colorants are all excipients.

[0054] The term "disintegrant" refers to an agent used in tablet pharmaceutical preparations that causes the tablet to disintegrate upon contact with moisture and release the pharmaceutically active ingredient.

[0055] The term "lubricant" refers to an agent added in small amounts to a tablet formulation to reduce friction and improve the manufacturing process.

[0056] The term "filler" refers to an agent added to a tablet formulation to increase the bulk of material that must be formulated to facilitate processing.

[0057] The term "binder" refers to an agent which ensures that a tablet having the required mechanical strength is produced.

[0058] Unless otherwise stated, in the context of the present invention, when indicating that a composition "comprises" one or more than one other component / element, it means that the indicated component / element must be present in the composition, and in addition to the specifically indicated component / element, other components may also be present in the composition, but are not required to be present. In other words, indicating that a composition "comprises" one or more than one component does not exclude that the composition consists of or essentially consists of the mentioned component.

[0059] Unless otherwise stated, in the context of the present invention, the percentage and amount of a certain component in a composition refers to the weight of the component relative to the total weight of the composition.

[0060] Unless otherwise indicated, in the context of the present invention, a numerical range indicated for a parameter such as the weight or volume of a component in a mixture includes the upper and lower limits of the range, e.g., if the weight or volume content of component A in a mixture is indicated as "X to Y", the content of A may be X, Y or any intermediate value.

[0061] Unless otherwise stated, data relating to peaks in XRPD patterns refer to peaks measured at room temperature using copper Kα radiation within the usual uncertainty limits due to instrumental measurements. During acquisition, it is typically 2θ ± 0.2 degrees.

[0062] In one aspect, the present invention provides novel N-[(2S)-1-[3-(3-chloro-4-cyanophenyl)-1H-pyrazol-1-yl]-propan-2-yl]-5-(1-hydroxyethyl)-1H-pyrazole-3-carboxamide (darolamide), referred to herein as nanocrystalline form or NC form or NC form, wherein the nanocrystalline form is characterized by having about 40 m 2 / g to about 150m 2 / g, preferably about 50m 2 / g to about 135m 2 / g, more preferably about 60m 2 / g to about 135m 2 The specific surface area (SSA) of / g is analyzed using a multi-point nitrogen adsorption technique based on the Brunauer, Emmett and Teller (BET) theory, for example using a TriStar (II) automatic gas adsorption analyzer (Micromeritics, Inc.). The samples are suitably vacuum dried at 45°C overnight. As described in the experimental section, the volumetric method can be used at a relative pressure of 0.05 p / p0 to 0.3 p / p0.

[0063] Specific surface area is an important physical property of active pharmaceutical ingredients. This parameter greatly affects the preparation process of the drug, such as filtration, purification, blending, tableting, and the characteristics of the active pharmaceutical ingredient, especially its dissolution rate, and thus its bioavailability, which is well known in the art, for example, see Kyung Rok Chu et al. Effect of particle size on the dissolution behaviours of poorly water-soluble drugs, Arch. Pharm. Res., July 2012, 35 (7), 1187-95, DOI 10.1007 / s12272-012-0709-3.

[0064] The results described in Example 3 show that the nanocrystalline form (NC form) of the present invention exhibits a higher SSA value as shown in Comparative Examples 1a and 2, if compared with samples of type I and rounded crystalline particles synthesized according to the teachings of patent applications WO2016 / 120530 and WO2018 / 162793, respectively.

[0065] Furthermore, the SSA values ​​calculated for the samples of form I and rounded crystalline particles obtained from comparative examples 1a and 2, respectively, are consistent with the values ​​disclosed in the WO2018 / 162793 patent application and the values ​​reported in Annex 1 prepared by the applicant of that application during the examination in the European phase. As described in comparative examples 1b and 1c, the form I prepared according to WO2016 / 120530 was also ground according to the teaching of EP3495352A1 (manual grinding in a mortar for 5 minutes) and by instrumental techniques (micronization by means of an FPS Q-Mill device): the samples obtained showed the same polycrystalline form I, but with a lower degree of crystallinity (thus potentially generating stability problems), while the SSA increased only very slightly with respect to the starting material, still well below the values ​​characteristic of the NC form of the invention.

[0066] This indicates that darolutamide having a higher surface area cannot be obtained from the previously known Form I by simple conventional techniques, whereas the NC Form of the present invention has an advantageously higher SSA by its own nature.

[0067] In another aspect of the present invention, the nanocrystalline form has a higher solubility in physiologically relevant aqueous media compared to type I and round crystalline particles. The following solubility test was performed: all samples were dissolved in aqueous media at pH 1.0 and pH 7.5 at 37°C and atmospheric pressure, and the concentration of saturated darolamide solution relative to an external reference standard was determined by HPLC test under stirring in the presence of undissolved substances. The results showed that after 60 minutes, type I and round crystalline particles showed the same solubility at both pH values, while the solubility of the nanocrystalline form of the present invention was eight times higher. In addition, under both pH conditions, the equilibrium solubility concentration of type I and round crystalline particles after 5 minutes was 0.02 mg / mL, and this concentration value remained unchanged at the time points of 10 minutes and 60 minutes, while the solubility of the nanocrystalline form of the present invention after 5 minutes was 0.12 mg / mL to 0.16 mg / mL. These results are particularly important for BCS class II substances such as darolutamide, because the bioavailability of such drugs can be improved by increasing the solubility and dissolution rate of the drug in gastrointestinal fluid. It is well known that a rate-limiting step for such drugs is solubility in gastric fluid, not absorption. Therefore, increasing solubility improves bioavailability, which can significantly reduce the daily dose and actually reduce adverse reactions in patients.

[0068] In a specific aspect, the nanocrystalline form of darolutamide is further characterized in that when the nanocrystalline form is viewed at room temperature with a wavelength of When measured with Cu-Kα radiation, the powder X-ray diffraction pattern includes broad peaks at 2θ of 10.2±0.2 degrees, 14.4±0.2 degrees and 17.8±0.2 degrees.

[0069] Preferably, the crystalline form of darolutamide is characterized in that when the crystalline form of darolutamide is subjected to a wavelength of Its powder X-ray diffraction pattern also includes broad peaks at 2θ of 8.6±0.2 degrees and 23.6±0.2 degrees each when measured with Cu-Kα radiation.

[0070] In another specific aspect, the crystalline form of darolutamide is characterized in that when measured at room temperature with a wavelength of When measured with Cu-Kα radiation, its powder X-ray diffraction pattern includes at least one of broad peaks with 2θ values ​​of 6.2±0.2 degrees, 16.3±0.2 degrees and 22.2±0.2 degrees.

[0071] In another specific aspect, the nanocrystalline form of darolutamide is characterized by having Figure 1 X-ray diffraction pattern shown.

[0072] As a non-limiting example, Table 1 below provides a list of peak positions of representative XRPD patterns associated with the nanocrystalline form. The peaks in the XRPD patterns of Table 1 are intended to encompass peaks measured by an instrument using copper Kα radiation at room temperature. The acquisition results in a typical uncertainty range of ±0.2 degrees 2θ.

[0073] Table 1

[0074] Peak number 2θ[°] 1 6.2 2 8.6 3 10.2 4 14.4 5 16.3 6 17.8 7 22.2 8 23.6

[0075] In other specific aspects, the nanocrystalline form of darolutamide is characterized in that its DSC curve shows a broad endothermic transition with a peak temperature of about 130°C to about 150°C when measured using DSC at a heating rate of 10°C / minute. This transition is associated with the melting of the nanocrystalline form of the present invention. In another specific aspect, darolutamide is characterized in that its DSC curve shows a broad endothermic transition with a peak temperature of about 130°C to about 150°C when measured using DSC at a heating rate of 10°C / minute, followed by an exothermic transition with a peak temperature of about 140°C to about 155°C, followed by another endothermic transition with a peak temperature of about 160°C to about 180°C, preferably about 164°C to about 176°C. In another specific aspect, the first and second thermal events can be only partially resolved.

[0076] In other specific aspects, the nanocrystalline form of darolutamide is characterized by having Figure 2 DSC thermogram shown.

[0077] In yet another particular aspect, the thermal events can show relative intensity changes if compared to one another.

[0078] In another specific aspect, the nanocrystalline form of darolamide is characterized by having peaks including 163.3 ± 0.2 ppm, 107.3 ± 0.2 ppm, 102.4 ± 0.2 ppm, and 57.4 ± 0.2 ppm. 13 C CPMAS NMR spectroscopy.

[0079] In another specific aspect, the nanocrystalline form of darolutamide is characterized by 13 The C CPMAS NMR spectrum also includes peaks at 19.5±0.2 ppm, 47.4±0.2 ppm, 62.2±0.2 ppm, 104.8±0.2 ppm, 111.1±0.2 ppm, 115.0±0.2 ppm, 122.5±0.2 ppm, 126.2±0.2 ppm, 134.1±0.2 ppm, 139.2±0.2 ppm, 148.0±0.2 ppm, 152.1±0.2 ppm, and 162.4±0.2 ppm.

[0080] In yet another specific aspect, the nanocrystalline form of darolutamide is characterized by having Figure 3 shown 13 C CPMA S NMR spectroscopy.

[0081] In another specific aspect, the nanocrystalline form of darolutamide is characterized by having Figure 4 Infrared spectrum shown.

[0082] In yet another specific aspect, the crystallite size of the nanocrystalline form according to the present invention calculated by the Scheele equation is about 5 nm to about 11 nm, preferably about 6 nm to about 8 nm.

[0083] The Scheele equation was applied to the most separated and sharp peaks in the X-ray spectrum of the nanocrystal form, and the slightly asymmetric peak shape was described as "split pseudo-Voigt" using the spectrum fitting (PF) technique to better determine the experimentally measured peak width values, which is necessary for calculating the crystallite size, as reported in the experimental section. The estimated grain size obtained by the mathematical method is consistent with the size of the microstructure observed using a scanning electron microscope (SEM). According to Figure 5 From the SEM images shown, it can be concluded that when zoomed in to 1 μm, the sample presents a complex framework composed of very fine filaments of submicron size, which in turn are formed by other substructures of significantly smaller size, well below 30 nm. Down to the 30 nm limit, no morphologically crystalline particles can be observed, indicating that, consistent with the XRPD results, this material is definitely nanoscale.

[0084] On the other hand, the crystalline form according to the invention is chemically and physically stable: as reported in the experimental part, after storage for several months at 25°C and 40°C / 75% RH, there is no change in its polymorphic form as assessed by X-ray powder diffraction (XRPD) and no reduction in its chemical purity as measured by high performance liquid chromatography (HPLC) analysis.

[0085] In another aspect, the present invention relates to a method for preparing a nanocrystalline form of darolutamide, comprising the following steps:

[0086] (i) providing a solution of darolamide in an organic solvent selected from the group consisting of 2-methyltetrahydrofuran, tetrahydrofuran, dihydrogen sulfoxide, Alkane and any mixture thereof, wherein the water content in the solution is from about 2% to about 20% by weight of the total solution;

[0087] (ii) optionally, filtering;

[0088] (iii) cooling the resulting solution to -5°C / 15°C;

[0089] (iv) optionally, seeding the crystals before or during the antisolvent addition process described in (v);

[0090] (v) adding an antisolvent selected from C5 to C7 linear or branched alkanes, cycloalkanes, substituted cycloalkanes, toluene, symmetrical ethers and asymmetrical ethers, characterized in that the temperature of the mixture is maintained at -5°C to 15°C during the addition;

[0091] (vi) optionally, adding a further portion of the antisolvent used in step (v) to completely precipitate the solid;

[0092] (vii) recovering the resulting solid and, optionally, drying it.

[0093] Daroltamide used in the above process can be prepared according to one of the teachings disclosed in the prior art or, preferably, by reduction of daroltamide ketone of formula (II) according to the procedure reported in the experimental part (Examples 12a to 12e).

[0094] Darolimide can be synthesized according to one of the teachings disclosed in the prior art, in particular following the procedure reported in Example 34 of WO2011 / 051540.

[0095] In another specific aspect, step (i) of the above method is carried out using a solution provided by dissolving darolamide in any solid form in an organic solvent selected from the group consisting of 2-methyltetrahydrofuran, tetrahydrofuran, dihydrogen sulfoxide, alkane and any mixture thereof, the water content in the solution is about 2 wt % to about 20 wt % of the total solution. In step (i), the total solution water content by weight can be measured according to the Karl Fischer method. The water content by weight is related to the water present when all components of the mixture, i.e., solvent, water and darolamide, are mixed together.

[0096] Optionally, if two phases are formed after step (i), a further step (i') may be performed, said step (i') comprising separating the phases and discarding the aqueous phase if present. The separation may be performed by decanting the phases and discarding the aqueous phase, as described below and included in the optional step (ix).

[0097] In yet another specific aspect, the solution provided in step (i) is maintained at a temperature of about 25° C. to about 70° C., more preferably about 45° C. to about 60° C., for about 30 minutes to completely dissolve the solids. The exact temperature required for dissolution also depends on the concentration of darolutamide used.

[0098] In other specific aspects, the concentration of darolamide in the solution in step (i) is generally about 160 g / L to about 30 g / L, preferably about 145 g / L to about 45 g / L, more preferably about 65 g / L to about 50 g / L. Most preferably, the concentration of darolamide in the solution in step (i) is about 65 g / L to about 45 g / L.

[0099] More preferably, step (i) is performed by providing a 2-methyltetrahydrofuran solution having a water content of about 2 wt % to about 20 wt % of the total solution, which can be measured according to Karl Fischer method at a temperature of about 45° C. to about 50° C., and a concentration of darolamide of about 65 g / L to about 50 g / L.

[0100] Optionally, the solution may be filtered (optional step (ii)) at the same temperature as the solution provided in step (i) to obtain a clear solution, removing any possible undissolved darolamide particles. Optionally, step (i') may be performed after the filtration of optional step (ii).

[0101] The solution is cooled to -5°C / 15°C (step iii) and optionally seeded (step iv) to promote crystallization and control the particle size of the resulting solid.

[0102] Depending on the total amount of darolutamide in the solution, about 1 wt % to about 10 wt % of seed crystals may be used for seeding. The seed crystals are typically nanocrystalline forms of the present invention.

[0103] The seeding process (iv) may be carried out before or during the addition of the antisolvent in step (v).

[0104] An antisolvent selected from C5 to C7 linear or branched alkanes, cycloalkanes, substituted cycloalkanes, toluene, symmetrical ethers and asymmetrical ethers is added to the solution obtained in step (iii), optionally with seeding, and the temperature of the mixture is maintained at about -5°C to about 15°C during the entire addition process, thereby initiating precipitation of the nanocrystalline form of darolutamide.

[0105] Preferably, the antisolvent is added in portions to maintain the correct temperature for the process. More preferably, a first portion of antisolvent is added, the solution is maintained under stirring for about 0.5 hour to about 3 hours, and then a second portion of antisolvent and a third portion of antisolvent are added to complete the precipitation.

[0106] The antisolvent-to-solvent volume ratio applied is generally from about 1:1 to about 3:1, preferably 2:1, wherein the solvent ratio is based on the volume of the organic solvent present in the solution provided in step (i).

[0107] The antisolvent is selected from C5 to C7 linear or branched alkanes, cycloalkanes, substituted cycloalkanes, toluene, symmetrical ethers and asymmetrical ethers. Preferably, the antisolvent is selected from heptane and toluene. More preferably, the antisolvent is heptane.

[0108] Preferably, the mixture obtained from step (v) is further stirred at a temperature of about -5°C to about 15°C for about 1 hour to about 24 hours, preferably about 3 hours to about 16 hours, so as to obtain the nanocrystalline form of darolutamide in high yield. The obtained nanocrystalline form of darolutamide is then recovered from the mixture of step (v) and optionally dried.

[0109] Preferably, the nanocrystalline form is separated from the mixture of step (v) by using any conventional method, such as filtration, centrifugation or decantation, more preferably by filtration or centrifugation, advantageously by filtration.

[0110] In a further step, the solid obtained may be washed with a suitable solvent, such as the antisolvent used to initiate the crystallization in step (v).

[0111] Optionally, the obtained nanocrystalline form is dried using conventional methods, for example, at a temperature of about 20° C. to about 60° C., preferably about 30° C. to about 45° C., under vacuum. Typically, the drying time is about 6 hours to about 72 hours, preferably about 10 hours to about 48 hours, and more preferably about 12 hours to about 24 hours.

[0112] In another aspect of the present invention, the solution of step (i) is obtained by the steps comprising:

[0113] (viii) providing darolutamide dissolved in a mixture of an organic solvent and water, wherein the organic solvent is selected from 2-methyltetrahydrofuran, tetrahydrofuran, dihydrofuran, Alkanes and any mixtures thereof, wherein the amount of water is up to 20% by weight of the total mixture, as measured, for example, according to the Karl Fischer method;

[0114] (ix) if two phases are present, decanting the phases and discarding the aqueous layer;

[0115] (x) optionally, distilling the organic solvent at ambient pressure until a residual solution having a darolutamide concentration of about 160 g / L to about 30 g / L is obtained;

[0116] (xi) Optionally, adding another portion of fresh organic solvent or mixture thereof used in step (viii) and performing step x to obtain a solution having a water content of 2 to 20 wt % of the total solution, the weight percentage being measured, for example, according to Karl Fischer method.

[0117] In a specific aspect, the mixture provided in step (viii) is maintained at a temperature of about 25°C to about 70°C, more preferably about 45°C to about 60°C, for about 30 minutes to allow complete dissolution of darolutamide.

[0118] In another specific aspect, the mixture provided in step (viii) of the above method is obtained by dissolving any solid form of darolamide in a mixture of an organic solvent and water, wherein the organic solvent is selected from 2-methyltetrahydrofuran, tetrahydrofuran, dihydrogen sulfoxide, Alkanes and any mixtures thereof, wherein the amount of water, calculated as a percentage, is up to 20% by weight of the total mixture. The water content can be measured, for example, according to the Karl Fischer method.

[0119] Optionally, the darolutamide mixture in step (viii) is obtained directly from the organic layer produced by the reaction process leading to obtaining the product darolutamide.

[0120] Preferably, the darolamide mixture in step (viii) is obtained directly from the organic layer produced by the reduction reaction process of darolamide ketone of formula (II), wherein the reaction is carried out in the presence of a hydride as a reducing agent in 2-methyltetrahydrofuran, tetrahydrofuran, dihydrogen sulfoxide, alkanes or mixtures thereof and water.

[0121] More preferably, the reduction reaction is carried out using sodium borohydride as a reducing agent in 2-methyltetrahydrofuran or dihydrogen phosphate. It is carried out in alkane and water.

[0122] Optionally, sodium borohydride is added portionwise to the solution containing darolutamide at room temperature.

[0123] The reaction mixture is stirred for about 3 hours to 10 hours until complete conversion is achieved, with the temperature maintained at about 20° C. to about 50° C., preferably at room temperature. Optionally, the reaction is carried out by adding a 1 N HCl solution and stirring the mixture at room temperature for about 15 minutes to about 30 minutes. The aqueous phase is then discarded and water is added up to 20% by weight of the total weight of the organic phase to provide a solution that is used directly in step (viii).

[0124] The resulting solution is then decanted and the aqueous layer discarded, and during all operations of step (ix) the temperature is maintained at about 25°C to about 70°C, more preferably about 45°C to about 60°C, for about 30 minutes to allow complete dissolution of darolutamide.

[0125] Optionally, in step (x), the obtained organic layer is distilled at ambient pressure until a residual solution having a darolamide concentration of 160 g / L to 30 g / L, preferably 145 g / L to about 45 g / L, more preferably about 65 g / L to about 50 g / L is obtained.

[0126] Optionally, another portion of a new organic solvent or a mixture thereof selected from the solvent used in step (viii) is added, and step (x) is performed again to obtain a solution having a darolamide concentration of 160 g / L to 30 g / L, preferably 145 g / L to about 45 g / L, more preferably about 65 g / L to about 50 g / L, the water content of the solution being about 2 wt % to about 20 wt % of the total solution, for example, measured according to the Karl Fischer method. The amount of the new organic solvent or a mixture thereof selected from the solvent used in step (viii) is about 1:10 to about 4:10, calculated as a volume ratio relative to the total volume of the same solvent or a mixture thereof used in step (viii). In another specific aspect, the volume ratio of the new organic solvent or a mixture thereof selected from the solvent used in step (viii) includes any two of the following: 1.3:10, 2:10, 3:10.

[0127] In another aspect, the present invention provides a pharmaceutical formulation comprising a nanocrystalline form of darolutamide and optionally at least one excipient.

[0128] The formulation can be suitably prepared, for example, by mixing the nanocrystalline form of darolutamide with one or more than one pharmaceutically acceptable excipient conventionally used in formulations in an amount of about 25% to about 75%, preferably about 35% to about 55%, based on the total weight of the pharmaceutical composition.

[0129] On the other hand, the nanocrystalline form of the present invention can be formulated into a tablet comprising at least one pharmaceutically acceptable excipient suitable for its preparation and a nanocrystalline form of darolamide, wherein the amount of the nanocrystalline form is about 25% to about 75%, preferably about 35% to about 55%, based on the total weight of the tablet.

[0130] Tablets can be prepared by conventional methods known in the art.

[0131] A suitable method is a wet granulation technique, as shown in the non-limiting examples reported in the experimental section. The formulation can be suitably prepared by first mixing the nanocrystalline form of darolamide with the desired excipients, preferably at least one filler such as anhydrous lactose monohydrate, calcium hydrogen phosphate and mixtures thereof, at least one binder such as povidone, and a first portion of a disintegrant. The disintegrant is added in an amount of 0.2% to 0.8% by weight, preferably, the disintegrant is cross-linked sodium carboxymethyl cellulose. The mixture is then granulated in a suitable granulator container, such as a wet high shear granulator, using purified water as the granulation liquid. The wet granules can be dried, preferably in a fluidized bed dryer, and the remaining disintegrant is then added to the granules. A lubricant such as magnesium stearate is then added to the material of the previous step and blended. The granules are then pressed into tablets.

[0132] In yet another aspect, the present invention provides a pharmaceutical formulation comprising a uniform solid dispersion of darolutamide obtained by grinding the nanocrystalline form using conventional grinding techniques such as a fluid jet mill. The grinding technique can produce a relatively fine pharmaceutical powder with a final particle size within the range required to support the preparation of a mixture for tablet formulation.

[0133] In yet another specific aspect, the present invention provides a tablet coated with a film to facilitate swallowing of the tablet, comprising the nanocrystalline form of darolutamide and optionally at least one excipient.

[0134] The following non-limiting examples are illustrative of the present disclosure and should not be construed as limiting the scope of the invention in any way.

[0135] Experimental Section

[0136] Example 1a (Comparative): Preparation of Darolutamide Type I

[0137] (Repeat Example 1 of WO2016 / 120530)

[0138] 40.0 g of darolamide, water (30 mL) and acetonitrile (570 mL) were added to a 1000 mL glass reactor, and the resulting mixture was dissolved by heating at 78°C. The solution was cooled to room temperature under stirring and stirred at the same temperature for 3 days. The resulting suspension was filtered and the solid filter cake was washed with 160 mL of acetonitrile: water (95:5) mixture. The wet solid was dried at 40°C for 12 hours and then at 60°C for 2 hours under vacuum to obtain 38.4 g (y = 90.6%) of darolamide. The XRPD trace of the obtained sample is shown in Fig.13 .

[0139] Example 1b (Comparative): Manual grinding of darolamide type I

[0140] (Repeat Example 13 of EP3495352A1)

[0141] About 50 mg of darolamide Form I prepared according to WO2016 / 120530 was manually ground in a mortar for 5 minutes; the resulting solid was analyzed by XRPD ( Fig.13 XRPD traces are reported in ).

[0142] This procedure was repeated with 4 g quantities to obtain sufficient material for SSA determination of the resulting solid (data reported in Table 2 of Example 13).

[0143] Example 1c (Comparative): Instrumental Grinding of Darolutamide Type I

[0144] (Similar to Example 13 in EP3495352A1, except that a grinding device is used)

[0145] About 10 g of darolamide Form I prepared according to WO2016 / 120530 was milled in an FPS Q-Mill 2 apparatus using the following instrument parameters:

[0146]

[0147] The ground solid was subjected to XRPD analysis (XRPD traces reported at Fig.13 ) and SSA determination (data reported in Table 2 of Example 13).

[0148] Example 2 (Comparative): Preparation of round crystalline particles

[0149] (Repeat Example 3 of WO2018 / 162793)

[0150] 15.0 g of darolamide, water (100 mL) and ethanol (110 mL) were added to a 500 mL glass reactor and the resulting mixture was dissolved by heating to 75 ° C. 786 mg of activated carbon SX Ultra and 1.5 g of diatomaceous earth were added and then stirred for 1 hour. The suspension was then filtered while hot and the filtrate was transferred to a 500 mL glass reactor. The carbon / diatomaceous earth filter cake was washed with 15.5 mL of ethanol. The resulting washing liquid was added to the solution in the glass reactor. The solution was then cooled to 70 ° C within 10 minutes and then cooled to 60 ° C within 10 minutes. The solution was then cooled to 30 ° C while 75 mL of water was added. The resulting suspension was stirred for another 30 minutes, the precipitate was filtered, and the resulting solid filter cake was washed with water. The wet solid was dried in vacuo at 70 ° C to obtain 12.38 g (y = 82.5%) of darolamide.

[0151] Example 3: Preparation of Nanocrystalline Forms of Darolutamide Starting from the Solid Form of Darolutamide

[0152] 100 g of darolamide was suspended in 2-methyltetrahydrofuran (1000 mL) and water (200 mL), and the mixture was heated to 45°C to 50°C until complete dissolution of the solid was observed. The clear phases were separated: the bottom aqueous phase was discarded, and the organic layer was distilled at ambient pressure until a residual volume of about 700 mL was reached. 2-methyltetrahydrofuran (300 mL) was added to the solution, and the mixture was then distilled again at ambient pressure until a residual volume of about 700 mL was reached. The resulting solution had a water content of about 2.6% as measured by Karl Fischer analysis, was filtered and cooled to -5°C / 5°C, and then heptane (200 mL) was added dropwise over about 15 minutes. The mixture was stirred at -5°C / 5°C for at least 3 hours. Heptane (1200 mL) was added dropwise to the resulting suspension over about 30 minutes, and the mixture was stirred at -5°C / 5°C for at least 16 hours. The suspension was filtered and the solid was washed with heptane (300 mL). The wet product was dried under vacuum at 50° C. for 17 to 20 hours until the weight was constant, thereby obtaining about 90 g (y=90.0%) of nanocrystalline form of darolamide in the form of off-white powder.

[0153] Example 4: Preparation of Nanocrystalline Forms of Darolutamide Starting from the Solid Form of Darolutamide

[0154] 100 g of darolamide was suspended in 2-methyltetrahydrofuran (1000 mL) and water (200 mL), and the mixture was heated to 45°C to 50°C until complete dissolution of the solid was observed. The clear phases were separated: the bottom aqueous phase was discarded and the organic layer was distilled at ambient pressure until a residual volume of about 700 mL was reached. 2-Methyltetrahydrofuran (200 mL) was added to the solution, and the mixture was distilled again at ambient pressure until a residual volume of about 700 mL was reached. The water content of the resulting solution was measured by Karl Fischer analysis to be about 3.6%, cooled to -5°C / 5°C, and then seeds of the nanocrystalline form of darolamide (1% weight / weight) were added. The resulting suspension was stirred at this temperature for 15 minutes to 20 minutes, and then heptane (200 mL) was added dropwise over about 30 minutes. The mixture was stirred at -5°C / 5°C for at least 3 hours. Heptane (1200 mL) was added dropwise to the resulting suspension over about 30 minutes, and the mixture was stirred at -5°C / 5°C for at least 16 hours. The suspension was filtered and the solid was washed with heptane (300 mL). The wet product was dried under vacuum at 50°C for 17 to 20 hours until the weight was constant. About 92 g (y = 92.0%) of the nanocrystalline form of darolamide in the form of an off-white powder was obtained.

[0155] Example 5: Preparation of Nanocrystalline Forms of Darolutamide Starting from the Solid Form of Darolutamide

[0156] 50 g of darolamide was suspended in 2-methyltetrahydrofuran (500 mL) and water (100 mL), and the mixture was heated to 45°C to 50°C until complete dissolution of the solid was observed. The clear phases were separated: the bottom aqueous phase was discarded, and the organic layer was distilled at ambient pressure until a residual volume of about 350 mL was reached. The water content of the resulting solution was measured to be about 5.7% by Karl Fischer analysis, cooled to -5°C / 5°C, and then heptane (200 mL) was added dropwise over about 30 minutes. The mixture was stirred at -5°C / 5°C for at least 3 hours. Heptane (250 mL) was added dropwise to the resulting suspension over about 30 minutes, and the mixture was stirred at -5°C / 5°C for at least 1 hour. Another portion of heptane (250 mL) was added over about 30 minutes, and the mixture was stirred at -5°C / 5°C for at least 16 hours. The suspension was filtered and the solid was washed with heptane (150 mL). The wet product was dried under vacuum at 50° C. for 17 to 20 hours until the weight was constant, thereby obtaining about 45 g (y=90%) of nanocrystalline form of darolamide in the form of off-white powder.

[0157] Example 6: Preparation of Nanocrystalline Forms of Darolutamide Starting from the Solid Form of Darolutamide

[0158] 3 g of darolamide was suspended in 2-methyltetrahydrofuran (30 mL) and water (6 mL), and the mixture was heated to 45°C to 50°C until complete dissolution of the solid was observed. The clear phases were separated: the bottom aqueous phase was discarded, and the organic layer was distilled at ambient pressure until a residual volume of about 22 mL was reached. The water content of the resulting solution was measured to be about 5.8% by Karl Fischer analysis and filtered. The filtrate was cooled to 0°C to 10°C, and then heptane (42 mL) was added dropwise over about 60 minutes. The mixture was stirred at 0°C to 10°C for at least 16 hours. The suspension was filtered and the solid was washed with heptane (10 mL). The wet product was vacuum dried at 50°C for 17 to 20 hours until the weight was constant. About 2.5 g (y = 83.3%) of a nanocrystalline form of darolamide in the form of an off-white powder was obtained.

[0159] Example 7: Preparation of Nanocrystalline Forms of Darolutamide Starting from the Solid Form of Darolutamide

[0160] 30 g of darolamide was suspended in 2-methyltetrahydrofuran (450 mL) and water (60 mL), and the mixture was heated to 45°C to 50°C until complete dissolution of the solid was observed. The clear phases were separated: the bottom aqueous phase was discarded, and the organic layer was distilled at ambient pressure until a residual volume of about 300 mL was reached. 2-Methyltetrahydrofuran (60 mL) was added to the solution, and the mixture was distilled again at ambient pressure until a residual volume of about 300 mL was reached. The water content of the resulting solution was measured by Karl Fischer analysis to be about 3.7%, filtered and cooled to 0°C to 10°C. Heptane (600 mL) was added dropwise over about 60 minutes. The mixture was stirred at 0°C to 10°C for at least 16 hours. The suspension was filtered and the solid was washed with heptane (90 mL). The wet product was dried under vacuum at 50°C for 17 to 20 hours until the weight was constant. About 29 g (y=96.7%) of the nanocrystalline form of darolamide in the form of off-white powder was obtained.

[0161] Example 8: Preparation of Nanocrystalline Forms of Darolutamide Starting from the Solid Form of Darolutamide

[0162] 40 g of darolamide was suspended in 2-methyltetrahydrofuran (400 mL), and water was then added until a water content of about 4.3 wt % of the total solution was obtained, as measured by Karl Fischer. The mixture was heated to 45°C to 50°C until complete dissolution of the solid was observed, and then filtered and cooled to 0°C to 10°C. Seed crystals of the nanocrystalline form of darolamide (2% weight / weight) were added, and then 800 mL of heptane was added dropwise over about 60 minutes. The mixture was stirred at 0°C to 10°C for at least 20 hours. The suspension was filtered and the solid was washed with heptane (100 mL). The wet product was vacuum dried at 50°C for 17 to 20 hours until the weight remained constant. About 35 g (y=87.5%) of the nanocrystalline form of darolamide was obtained as an off-white powder.

[0163] Example 9: Preparation of Nanocrystalline Forms of Darolutamide Starting from the Solid Form of Darolutamide

[0164] 20 g of darolamide was suspended in 2-methyltetrahydrofuran (200 mL) and water (40 mL), and the mixture was heated to 45°C to 50°C until complete dissolution of the solid was observed. The resulting clear phase was separated: the bottom aqueous phase was discarded. 2-Methyltetrahydrofuran (40 mL) was added to the solution, and the mixture was then distilled at ambient pressure until a residual volume of about 140 mL was reached. 2-Methyltetrahydrofuran (40 mL) was added to the solution, and the mixture was then distilled at ambient pressure until a residual volume of about 140 mL was reached. The resulting solution had a water content of about 3.4% as measured by Karl Fischer analysis, was cooled to 0°C to 5°C, and then seed crystals of the nanocrystalline form of darolamide (1% weight / weight) were added. The resulting suspension was stirred at this temperature for 15 minutes to 20 minutes, and then toluene (40 mL) was added dropwise over about 30 minutes. The mixture was stirred at 0°C to 5°C for at least 3 hours. Toluene (240 mL) was added dropwise to the resulting suspension over a period of about 30 minutes, and the mixture was stirred at 0° C. to 5° C. for about 16 hours. The suspension was filtered and the solid was washed with toluene (60 mL). The wet product was dried under vacuum at 50° C. for 17 to 20 hours until the weight was constant. About 18 g (y=90.0%) of the nanocrystalline form of darolamide in the form of an off-white powder was obtained.

[0165] Example 10: Preparation of 3-acetyl-N-[(2S)-1-[3-(3-chloro-4-cyanophenyl)pyrazol-1-yl]propan-2-yl]-1H-pyrazole-5-yl The darolamide solution directly obtained by the reduction of formamide (darolamide ketone) begins to prepare the nanocrystalline form of darolamide.

[0166] 20 g (50.4 mmol) of darotamidone, 300 mL of 2-methyltetrahydrofuran and 40 mL of water were added to a glass reactor. NaBH4 (1.42 g, 37.5 mmol) was added in one portion at room temperature and the mixture was stirred at the same temperature for 17 hours. 1 N HCl was added to a pH of about 4 and the mixture was stirred for about 15 minutes, then the aqueous phase was discarded and the organic phase was washed twice with 100 mL of H2O at 55°C to 60°C.

[0167] The organic phase was distilled under atmospheric pressure until a solution of 200 mL was obtained. 40 mL of 2-methyltetrahydrofuran was added to the solution, and the solvent was distilled again to obtain a residue of 140 mL, which had a water content of about 2.5% as determined by KF analysis. The solution was then cooled to 0 to 5 ° C, and 40 mL of heptane was added in about 15 to 20 minutes. The suspension was stirred at 0 to 5 ° C for 3 hours, and additional heptane (240 mL) was then added in about 30 minutes to complete precipitation. The suspension was stirred at a temperature of 0 to 5 ° C for 14 hours, and solids were then recovered by filtration. The solid filter cake was washed with 80 mL of heptane, and the wet solid was dried in a vacuum oven at 50 ° C for about 16 hours.

[0168] Example 11: Preparation of 3-acetyl-N-[(2S)-1-[3-(3-chloro-4-cyanophenyl)pyrazol-1-yl]propan-2-yl]-1H-pyrazole-5-yl The darotamide solution obtained directly by reduction of formamide (darotamide ketone) is used to prepare the nanocrystalline form of darotamide

[0169] 50 g (126.0 mmol) of darotamidone, 750 mL of 2-methyltetrahydrofuran and 100 mL of water were added to a glass reactor. NaBH4 (3.60 g, 95.2 mmol) was added in one portion at room temperature and the mixture was stirred at the same temperature for 17 hours. 1 N HCl was added to a pH of about 4 and the mixture was stirred for about 20 minutes, then the aqueous phase was discarded and the organic phase was washed twice with 250 mL of H2O at 55°C to 60°C.

[0170] The organic phase was distilled at atmospheric pressure until 350 mL of a solution was obtained, which had a water content of about 5.9% as measured by KF analysis. The solution was then cooled to 0°C to 5°C and 700 mL of heptane was added over a period of about 3 to 4 hours. The suspension was stirred at a temperature of 0°C to 5°C for 14 hours and then the solid was recovered by filtration. The solid cake was washed with 200 mL of heptane and the wet solid was dried in a vacuum oven at 50°C for about 16 hours.

[0171] Example 12: 3-Acetyl-N-[(2S)-1-[3-(3-chloro-4-cyanophenyl)pyrazol-1-yl]propan-2-yl]-1H-pyrazole-5-carboxylate Reduction of amide (darotamide) in different solvents

[0172]

[0173] 12a: Reduction in 2-methyltetrahydrofuran

[0174] Under nitrogen, 8.93 g (22.5 mmol) of darotamide, 134 mL of 2-methyltetrahydrofuran and 18 mL of H2O were added to a 250 mL round-bottom flask equipped with a mechanical stirrer. NaBH4 (0.638 g, 16.85 mmol) was added to the resulting suspension in three portions at room temperature. The mixture was stirred for 5 hours. 1 N HCl was added to a pH of about 4, the mixture was stirred at room temperature for about 15 minutes, the aqueous phase was then discarded, and the organic phase was extracted twice with 20 mL of H2 at 55°C to 60°C. The resulting organic phase was evaporated in vacuo at 40°C to 45°C to give 8.2 g of darotamide as a white solid (reported at the end of the reduction process). 1 H NMR signal).

[0175] 12b: In 1,4-di Reduction in alkane

[0176] Under nitrogen atmosphere, 500 mg (1.26 mmol) of darotamide was suspended in 1,4-dihydropyridine. 1 mL of 1% ethyl acetate was added to a mixture of oxane (5 mL) and water (1 mL). NaBH4 (31 mg, 0.819 mmol) was added in one portion at room temperature and the mixture was stirred at the same temperature for 24 hours until complete conversion. 1 N HCl was added to a pH of about 1 to 2, the mixture was stirred for 1 hour, and then neutralized with 1 N NaOH. The distilled water was evaporated in vacuo at 40 to 45 °C. The aqueous residue was extracted with 2-methyltetrahydrofuran (10 mL); the organic layer was washed with water (10 mL), dried over Na2SO4, and evaporated in vacuo at 40°C to 45°C to give 500 mg of darolamide as a white solid (reported at the end of the reduction process). 1 H NMR signal).

[0177] 12c: Reduction in tetrahydrofuran

[0178] The reaction was carried out according to the procedure of Example 12b, using tetrahydrofuran instead of 1,4-dihydrofuran. Alkane was used as solvent. The mixture was stirred at room temperature for 24 hours until complete conversion. 1N HCl was added to a pH of about 1 to 2, the mixture was stirred at room temperature for 1 hour, and then neutralized with 1N NaOH. Tetrahydrofuran was evaporated in vacuo at 40°C to 45°C, and the aqueous residue was extracted with 2-methyltetrahydrofuran (10 mL); the organic layer was washed with water (10 mL), dried over Na2SO4, and evaporated in vacuo at 40°C to 45°C to obtain 480 mg of darolamide as a white solid (reported at the end of the reduction process). 1 H NMR signal).

[0179] 12d: Reduction in methyl tert-butyl ether

[0180] The reaction was carried out according to the procedure of Example 12b, using methyl tert-butyl ether instead of 1,4-dimethoxybenzene. Alkane was used as solvent. After 20 hours, the reaction mixture was still a suspension. Methyl tert-butyl ether (1.5 mL) and NaBH4 (16 mg) were added again and stirring was continued for 14 hours. After 4 hours, about 50% conversion was observed by HPLC analysis. 1N HCl was added to a pH of about 1 to 2. After 1 hour, the mixture was neutralized with 1N NaOH and filtered. The solid was purified using a preparative HPLC system to give 29 mg of darolamide as a white solid (reported at the end of the reduction process). 1 H NMR signal).

[0181] 12e: Reduction in cyclopentyl methyl ether

[0182] The reaction was carried out according to the procedure of Example 12b, using cyclopentyl methyl ether instead of 1,4-dimethoxybenzene. Alkane was used as solvent. After 20 hours, cyclopentyl methyl ether was added and the mixture was heated at 45°C for 4 hours and then at 65°C for another 4 hours. The solution was cooled to room temperature and then 16 mg of NaBH4 was added. After 16 hours, about 55% conversion was observed by HPLC analysis. 1N HCl was added to a pH of about 1 to 2. After 1 hour, the mixture was neutralized with 1N NaOH and filtered. The solid was purified using a preparative HPLC system to give 35 mg of darolamide as a white solid. 1 H NMR signals are reported below.

[0183] Darolamide 1 H NMR (500MHz, methanol-d4) δ8.05(dd,J=4.4,1.5Hz,1H),7.93(d,J=8.2Hz,1H),7.81(d,J=8.1Hz,1H),7.72(d,J=2.5Hz,1H),6.78(dd,J=2.4, 0.7Hz, 1H), 6.58 (s, 1H), 4.93 (q, J = 6.8Hz, 1H), 4.57 (m, 1H), 4.38 (qd, J = 13.8, 6.0Hz, 2H), 1.51 (d, J = 6.6Hz, 3H), 1.26 (d, J = 6.8Hz, 3H).

[0184] Example 13: Determination of specific surface area (SSA)

[0185] The specific surface areas of five batches of nanocrystalline forms of darolutamide prepared according to the present invention and the type I samples and round crystalline particles obtained in Comparative Examples 1 and 2, respectively, as comparisons were measured.

[0186] The specific surface area was measured using a TriStar (II) automatic gas adsorption analyzer (Micromeritics, Inc.) using a multi-point nitrogen adsorption technique based on the Brunauer, Emmett, and Teller (BET) theory. All samples were dried overnight in vacuum at 45 °C. 0 to 0.3p / p 0 The volume method was applied at a relative pressure of , and the specific surface area value was calculated using the “multi-point BET” calculation method based on 11 linear points within the above pressure range.

[0187] The results are reported in Table 2.

[0188] Table 2

[0189]

[0190] The results show that, if compared with the samples of type I and round crystalline particles obtained in Comparative Examples 1a and 2, respectively, and the samples of the ground or milled type I obtained in Comparative Examples 1b and 1c, the samples of the nanocrystalline form NC of darolamide according to the present invention exhibit higher specific surface area values ​​(thereby indicating that the ground or milled type I is a solid form different from the nanocrystalline form NC). In addition, the SSA values ​​of the samples of type I and round crystalline particles obtained in Comparative Examples 1a and 2, respectively, are similar to the SSA values ​​reported in the patent application WO2018 / 162793 and the Appendix 1 written by the applicant in the European phase examination of EP3592732 (Table 3).

[0191] Table 3

[0192]

[0193] Example 14: Comparison of solubility of nanocrystalline form, type I and round crystalline particles

[0194] The solubility of the nanocrystalline form of darolutamide according to the present invention and the type I and round crystalline particles obtained from Comparative Examples 1 and 2, respectively, was determined in the following aqueous media at selected pH: a buffer solution (hydrochloric acid 0.1 N) with a pH of 1.0 and a buffer solution with a pH of 7.5.

[0195] Under the above aqueous medium conditions, solubility data should be obtained by measuring the concentration of a stirred saturated darolamide solution in the presence of undissolved material by HPLC assay at 37°C and atmospheric pressure relative to an external reference standard (i.e. darolamide).

[0196] HPLC method

[0197] Equipment: Waters Alliance e2695 chromatograph (Waters) equipped with 2998 PDA UV-visible detector.

[0198] Software: Empower 3 Chromatography Data System (Waters)

[0199] Chromatographic column: XBridge Phenyl 3.5μm 4.6×150mm

[0200] Guard column: Gemini NX (Phenomenex) or similar products

[0201] Column temperature: 40°C

[0202] Ammonium formate solution: Dissolve 15.765 g of ammonium formate in 250 mL of water to prepare a 1 M ammonium formate solution (AF stock solution).

[0203] Mobile phase A: Dilute 10 mL of AF stock solution in 1000 mL of water. Adjust pH to 4.5.

[0204] Mobile phase B: methanol

[0205] Elution mode: Gradient

[0206] Time (minutes) A(%) B(%) 0 45 55 10 45 55 13 5 95 15 5 95 16 45 55 25 45 55

[0207] Sample plate temperature: 25°C

[0208] Injection volume: 5μL

[0209] UV detection: 280nm

[0210] Analysis time: 15 minutes

[0211] Total running time: 25 minutes

[0212] Under these conditions, the retention time (RT) of darolutamide was typically 7.8 minutes.

[0213] Prepare reference standard solution:

[0214] Eight reference standard solutions of different concentrations were accurately prepared and are reported as follows.

[0215] Daroltamide Reference Standard Solution "CRS 0.25" (0.25 mg / mL of daroltamide)

[0216] To a 100 mL volumetric flask, transfer 25 mg of darolamide standard (CRS) accurately weighed, then add about 80 mL of methanol, shake until completely dissolved, and dilute to the target volume with MeOH.

[0217] Daroltamide Reference Standard Solution "CRS 0.20" (0.20 mg / mL of daroltamide)

[0218] To a 10 mL volumetric flask, transfer 6 mL of "CRS 0.25" reference solution and dilute to target volume with methanol.

[0219] Daroltamide Reference Standard Solution "CRS 0.15" (0.15 mg / mL of daroltamide)

[0220] To a 25 mL volumetric flask, transfer 20 mL of "CRS 0.25" reference solution and dilute to target volume with methanol.

[0221] Daroltamide Reference Standard Solution "CRS 0.125" (0.125 mg / mL of daroltamide)

[0222] To a 20 mL volumetric flask, transfer 10 mL of "CRS 0.25" reference solution and dilute to the target volume with methanol.

[0223] Daroltamide Reference Standard Solution "CRS 0.10" (0.10 mg / mL of daroltamide)

[0224] To a 25 mL volumetric flask, transfer 10 mL of "CRS 0.25" reference solution and dilute to target volume with methanol.

[0225] Daroltamide Reference Standard Solution "CRS 0.075" (0.075 mg / mL of daroltamide)

[0226] To a 10 mL volumetric flask, transfer 3 mL of "CRS 0.25" reference solution and dilute to the target volume with methanol.

[0227] Daroltamide Reference Standard Solution "CRS 0.05" (0.05 mg / mL of daroltamide)

[0228] To a 50 mL volumetric flask, transfer 10 mL of "CRS 0.25" reference solution and dilute to target volume with methanol.

[0229] Daroltamide Reference Standard Solution "CRS 0.01" (0.01 mg / mL of daroltamide)

[0230] To a 10 mL volumetric flask, transfer 1 mL of "CRS 0.10" reference solution and dilute to the target volume with methanol.

[0231] Calibration curve

[0232] The linear response of the HPLC method was verified by injecting darolutamide reference solutions of known concentrations ranging from 0.01 mg / mL to 0.25 mg / mL.

[0233] All levels were injected three times, except for the 100% level which was injected six times to verify the % RSD of that level.

[0234] Linearity was assessed by visual inspection of the signal versus analyte concentration curve and then calculating the regression line using the least squares method. The results are shown in Table 4.

[0235] Table 4

[0236]

[0237] The regression equation is: A = -7196 + 21480639 * x

[0238] R 2 : 0.9999

[0239] The correlation coefficient r is greater than 0.990.

[0240] The 95% CI interval for the intercept of the regression line includes the value zero.

[0241] The method was adequately linear over the broad concentration range considered, from 0.01 mg / mL to 0.25 mg / mL.

[0242] Calibration curve see Figure 7 .

[0243] Test solution "T" of darolamide for determination of solubility

[0244] The samples of nanocrystalline form, type I and round crystalline particles of darutamide according to the present invention were prepared by transferring 100 mg of darutamide sample to a 40 mL test tube with a screw cap, adding 20 mL of dissolution medium, and placing the test tube in a water bath at 37° C. for magnetic stirring. After 5 minutes, 10 minutes and 60 minutes, an equal amount of the suspension (about 1.5 mL) was taken and filtered with a 0.45 μm filter (syringe filter device-PTFE membrane filter). The resulting clear solution was then injected as is or diluted with MeOH 0.8 mL to 1 mL and injected into HPLC.

[0245] The dissolution medium was prepared as follows:

[0246] - pH 7.5 buffer: Dissolve 1.38 g of sodium dihydrogen phosphate (NaH2PO4) in 180 mL of water, adjust the pH to 7.5 with 4N sodium hydroxide, and dilute to 1000 mL with water.

[0247] - pH 1.0 buffer: 0.1N hydrochloric acid commercial solution

[0248] Calculations and Reports:

[0249] The solution concentration is calculated according to the following formula:

[0250]

[0251] in:

[0252] C (mg / mL) is the concentration of darolamide in the studied dilution, in mg / mL;

[0253] AT is the peak area of ​​darolamide in the chromatogram of the test solution;

[0254] AR is the average value of the peak area of ​​darolamide in the chromatogram of the reference solution "CRS 0.10";

[0255] WR is the weight of darolamide CRS 0.10 in mg;

[0256] DR refers to the dilution starting from the nominal concentration of 25 mg (250 mL) to obtain a "CRS0.10" concentration of 0.10 mg / mL;

[0257] P is the potency of darolamide CRS (expressed as a percentage).

[0258] D1 is the dilution factor of the dacromet test sample in the HPLC vial and is calculated as follows:

[0259]

[0260] in:

[0261] VT is the volume of the test solution to be diluted (e.g. 0.8 mL);

[0262] Vf is the final volume (eg, 1 mL).

[0263] The solubility results are shown in the table below:

[0264] Table 5

[0265]

[0266] The solubility curves over time are reported in Figure 8 middle.

[0267] Example 15: XRPD analysis

[0268] XRPD analysis was performed at room temperature using a Bruker AXS D8 Advance diffractometer with θ / θ vertical scanning. The instrument was equipped with a Cu-Ka X-ray tube and operated at 40 kV / 40 mA to produce X-rays with radiation. The detector is a linear Lynxeye XE-T position sensor, 250 mm away from the sample. The powder sample is deposited on a 12 mm × 0.2 mm hollow sample holder consisting of a quartz single crystal zero background plate. The acquisition conditions of the diffraction data are as follows: the angle range 2θ is 2° to 40°, the scan is 0.02° / step, and the acquisition time is 1 s / step and 10 s / step. The instrument calibration is verified by NIST SRM 1976b. Data acquisition is performed using the Bruker Diffraction Measurement Center software, and data processing is performed using TOPAS software.

[0269] The XRPD pattern of the nanocrystalline form of darolutamide is characterized by very broad peaks, with a peak width of more than 1.0° in many cases. Examples of the pattern are Figure 1 shown.

[0270] Example 16: Determination of crystal domain size

[0271] The most separated and clear peaks in the X-ray diffraction pattern of the NC type: the peaks near about 8.6° and about 10.4° at 2θ, were used to calculate the crystal domain size using the Scheele equation.

[0272] In order to correctly determine the experimentally measurable peak width (HE) of the very broad peaks described above, a spectrum fitting (PF) technique was used to describe the slightly asymmetric peak shapes as "split pseudo-Voigt". For analytical descriptors of different peak shapes (such as Gaussian, Lorentzian, Voigt, pseudo-Voigt, Pearson VII or split versions), see RA Young and DB Wiles, 'Peak shapes functions in Rietveld refinement', J. Appl. Cryst., 1982, 15, 430-438.

[0273] Fig. 9 An example of a spectrum fitting graph related to a peak around 8.6° to 10.4° 2θ of darolutamide nanocrystals is shown.

[0274] Then calculate the average <he>= 1 / 2[HE(peak 1)+HE(peak 2)], and the instrument aberration (H I = 0.06° to 0.12°) corrected to the sample-dependent average value <hs>:

[0275]

[0276] Then use the Scheele equation <hs>Calculate the corresponding D value for each sample.

[0277] Due to H I Typically 0.06° to 0.12°, any HE value above 0.3° does not need to be converted to H S , so in the above case <hs> = <he>

[0278] The Scheele equation can be written as:

[0279] in:

[0280] D is the average size of the ordered (crystalline) domains;

[0281] k is the dimensionless shape factor, which is close to unity. The shape factor is typically around 0.9, but varies with the actual shape of the crystal;

[0282] λ is the wavelength of X-rays;

[0283] <hs>is the total peak width, approximated to the full width at half maximum (FWHM), corrected if necessary by subtracting instrumental line broadening, in radians;

[0284] θ is half of the diffraction angle 2θ.

[0285] Table 6 reports the calculated domain size values ​​for the nanocrystalline form of darolutamide from different batches.

[0286] Table 6

[0287]

[0288] Example 17: Characterization by Scanning Electron Microscope (SEM) Images

[0289] The nanocrystalline form of darolutamide according to the present invention was analyzed by scanning electron microscopy imaging. Figure 5 SEM images acquired at ×20,000 magnification are shown, and the scale bar is 1 μm.

[0290] The nanocrystalline form of darolutamide prepared according to the present invention exhibits a complex framework composed of filaments, which in turn are formed by other substructures of smaller size.

[0291] Example 18: DSC analysis

[0292] DSC analysis was performed using a Mettler DSC-1Star system, using a 40 μL standard aluminum crucible, loaded with about 3 mg to 6 mg of sample, sealed with a specific crucible seal press. An empty crucible of the same type was placed in the reference position of the DSC furnace. The reference material indium was used to calibrate the temperature scale and enthalpy response of the instrument. After opening a pinhole in the crucible cover, the sample was analyzed at a heating rate of 10 ° C / min under a nitrogen flow; the thermal range explored was 30 ° C to 250 ° C.

[0293] Figure 2 A non-limiting example of a DSC graph of a NC type is shown.

[0294] Embodiment 19: 13 C CPMAS NMR

[0295] All samples 13 C CPMAS NMR spectra were obtained using a Jeol ECZR 600 instrument. 1 H and 13 C core,operating at 600.17MHz and 150.91MHz respectively.

[0296] The powder samples were loaded into a cylindrical zirconia rotor with an outer diameter of 3.2 mm and a volume of 60 mL. A specific amount of each sample was collected and the rotor was filled without further preparation.

[0297] Acquired at room temperature with a rotation speed of 20 kHz 13 C CPMAS NMR spectra were acquired using a ramped cross-polarization pulse sequence, a 2.0 μs 90° 1H pulse, a 3.5 ms contact time, an optimized recycle delay of 2.2 s to 3.3 s, and 800 to 1200 scans, depending on the sample. A double pulse phase modulation (TPPM) decoupling scheme was used for each spectrum, with an RF field of 108.5 kHz. The 13C chemical shift scale was calibrated using the methylene signal of an external standard, glycine (43.7 ppm).

[0298] Table 7 shows the characteristics of the nanocrystalline forms of darolutamide in the samples 13 C Chemical shift values ​​(ppm) of peaks observed in CPMAS NMR spectra.

[0299] Table 7

[0300]

[0301] Figure 3 The nanocrystalline form of darolamide is shown 13 Example of C CPMAS NMR spectrum.

[0302] Example 20: Stability Study

[0303] Five equal portions of about 1 g of the nanocrystalline form of the present invention were stored under the following conditions, wherein RH refers to relative humidity:

[0304] -40℃ and 75%RH, double-layer PE bag in HDPE bottle

[0305] The samples were analyzed before storage (T0), after 1 month, 3 months, 6 months and 12 months of storage, the purity was controlled using high performance liquid chromatography (HPLC) and any changes in the crystalline form were evaluated using X-ray powder diffraction (XRPD) patterns.

[0306] HPLC analysis showed no significant decrease in the purity of the nanocrystalline form of the invention, both in terms of the formation of new impurities and in terms of an increase in the content of existing impurities, compared to the initial profile obtained at T0.

[0307] like Fig.10 The reported X-ray powder diffraction (XRPD) patterns recorded at the reported time points showed no signs of conversion to a different crystalline form.

[0308] Example 21: Identification The crystal form of darolamide contained in

[0309] The X-ray powder diffraction (XRPD) pattern The 300 mg drug product was compared to darolutamide Form I obtained according to the teachings of WO2016 / 120530. Fig.11 . Analytical samples of 300 mg were prepared by grinding drug tablets in an agate mortar to obtain a powder sample suitable for XRPD sampling.

[0310] At room temperature, the wavelength Cu-Kα radiation measurements When comparing the XRPD patterns of 300 mg of the drug product, by comparing the presented patterns, characteristic reflections of Type I can be detected at 2θ of 8.5±0.15 degrees, 10.4±0.15 degrees, 16.6±0.15 degrees, 16.9±0.15 degrees and 24.3±0.15 degrees.

[0311] Example 22: Preparation of tablets

[0312] Tablets of the nanocrystalline form of darolutamide were prepared using the ingredient list in Table 8 below.

[0313] Table 8

[0314]

[0315]

[0316] All ingredients except magnesium stearate were mixed in a high shear granulator, and only part of the croscarmellose sodium was added. Water was sprayed into the mixture for granulation. The granules were dried in a fluid bed dryer, and then the remaining croscarmellose sodium and magnesium stearate were added and mixed again.

[0317] The resulting mixture is compressed in a tablet press.

[0318] Optionally, the tablets are coated with a conventional coating agent until the weight gain is about 3%, more preferably polyvinyl alcohol iron oxide, talc and titanium dioxide are used as coating materials.

[0319] Example 23: Preparation of 3-acetyl-N-[(2S)-1-[3-(3-chloro-4-cyanophenyl)pyrazol-1-yl]propan-2-yl]-1H-pyrazole-5-yl The darotamide solution obtained directly by reduction of formamide (darotamide ketone) is used to prepare the nanocrystalline form of darotamide

[0320] 90 g (227 mmol) of darotamidone, 540 mL of 2-methyltetrahydrofuran and 45 mL of water were added to a glass reactor. A suspension of NaBH4 (8.60 g, 227 mmol) in 2-methyltetrahydrofuran was added four times at room temperature, and the mixture was stirred at the same temperature for 4 hours. 1N HCl was added to a pH of about 2, and the mixture was stirred at 20° C. to 30° C. for about 30 minutes, then the aqueous phase was discarded, the organic phase was diluted with 2-methyltetrahydrofuran (180 mL), and washed twice with water (180 mL each time).

[0321] The water content was about 12% as measured by KF analysis. The organic phase was filtered through diatomaceous earth and diluted with 2-methyltetrahydrofuran (450 mL) for washing the diatomaceous earth pad. The solution was then cooled to 5°C / 15°C, n-heptane (360 mL) was added, and then seed crystals of NC-type darolamide (2.7 g) were added. The mixture was cooled to -5°C / +5°C, and then n-heptane (990 mL) was added dropwise over about 2 hours while keeping the temperature below +5°C.

[0322] The resulting suspension was kept at -5°C / +5°C and stirred for 3 hours, and then the solid was recovered by filtration. The solid filter cake was washed with n-heptane (270 mL), and the wet solid was dried in a vacuum oven at 50°C for about 16 hours. NC-type darolamide (89.5 g) was obtained. The specific surface area (SSA) of the sample was 46.0 m 2 / g.

[0323] Example 24: Preparation of Nanocrystalline Forms of Darolutamide Starting from the Solid Form of Darolutamide

[0324] In a glass reactor, darolamide (90 g) was dissolved in a mixture of 2-methyltetrahydrofuran (1080 mL) and water (180 mL) with stirring at 20 / 30°C. The bottom aqueous layer was separated and discarded, and the remaining organic solution was filtered through a pad of celite, which was washed with 2-methyltetrahydrofuran (270 mL) and then combined with the residual solution. The solution was cooled to 5°C / 15°C, n-heptane (360 mL) was added, and then seed crystals of NC-type darolamide (2.7 g) were added. The mixture was cooled to -5°C / +5°C, and n-heptane (990 mL) was then added dropwise over about 2 hours while keeping the temperature below +5°C.

[0325] The resulting suspension was kept at -5°C / +5°C and stirred for 6 hours, and then the solid was recovered by filtration. The solid filter cake was washed with n-heptane (270 mL), and the wet solid was dried in a vacuum oven at 50°C for about 16 hours. NC-type darolamide (88 g) was obtained. The specific surface area (SSA) of the sample was 43.8 m 2 / g.

[0326] Reference List

[0327] Patent Literature:

[0328] WO2011 / 051540

[0329] WO2016 / 120530

[0330] WO2018 / 162793

[0331] ·EP3592732

[0332] EP3495352

[0333] Non-patent literature:

[0334] ·B.Movahedi, "Introductory Chapter: Nanocrystalline Materials", Nanocrystalline Materials, Feb. 2020, doi:10.5772 / intechopen.90255

[0335] ·Nasrollahzadeh, M. et al., "Chapter 2-Types of Nanostructures" "Interface Science and Technology", Volume 28, Chapter 2; 2019, Pages 29-80;

[0336] ·Suryanarayana, C., "Nanocrystalline Materials", International Materials Reviews, 1995, 40(2): 41-64

[0337] ·U.Holtzward and N.Gibson, 'The Scherrer equation versus the'Debye-Scherrerequation', Nature Nanotechnology, 2011, 6, 534.

[0338] ·Kyung Rok Chu et al., Effect of particle size on the dissolution behaviors ofpoorly water-soluble drugs, Arch.Pharm.Res., 2012July, 35(7), 1187-95, DOI10.1007 / s12272-012-0709-3.

[0339] For the sake of completeness, various aspects of the invention are set out in the following numbered clauses:

[0340] Item 1. A nanocrystalline form of N-[(2S)-1-[3-(3-chloro-4-cyanophenyl)-1H-pyrazol-1-yl]-propan-2-yl]-5-(1-hydroxyethyl)-1H-pyrazole-3-carboxamide (darolamide), characterized in that the nanocrystalline form has 50 m 2 / g to 150m 2 / g, preferably 60m 2 / g to 135m 2 The specific surface area (SSA) of 2.17 N 2 O 2 / g was measured using a multi-point nitrogen adsorption technique based on the Brunauer, Emmett and Teller (BET) theory.

[0341] Clause 2. The nanocrystalline form according to clause 1, characterized in that when the nanocrystalline form is subjected to a wavelength of When measured using Cu-Kα radiation, the powder X-ray diffraction pattern of the nanocrystalline form includes broad peaks with 2θ values ​​of 10.2±0.2 degrees, 14.4±0.2 degrees and 17.8±0.2 degrees.

[0342] Clause 3. The nanocrystalline form according to clause 2, characterized in that when the nanocrystalline form is subjected to a wavelength of When measured with Cu-Kα radiation, the powder X-ray diffraction pattern of the nanocrystalline form also includes each of the broad peaks with 2θ of 8.6±0.2 degrees and 23.6±0.2 degrees, and at least one of the following broad peaks with 2θ of 6.2±0.2 degrees, 16.3±0.2 degrees and 22.2±0.2 degrees.

[0343] Clause 4. The nanocrystalline form according to any one of the preceding clauses, characterized in that the nanocrystalline form has a crystallite size determined by the Scheele equation comprised between 5 nm and 11 nm, preferably between 6 nm and 8 nm.

[0344] Clause 5. The nanocrystalline form according to any one of the preceding clauses, characterized in that, when measured by DSC at a heating rate of 10°C / min, the nanocrystalline form has a DSC curve comprising a broad endothermic transition with a peak temperature of 130°C to 150°C.

[0345] Clause 6. A nanocrystalline form according to any one of the preceding clauses, characterized in that the nanocrystalline form has peaks at 163.3±0.2ppm, 107.3±0.2ppm, 102.4±0.2ppm and 57.4±0.2ppm. 13 C CPMA S NMR spectroscopy.

[0346] Clause 7. A method for preparing a nanocrystalline form as defined in any one of the preceding clauses, the method comprising the following steps:

[0347] (i) providing a solution of darolamide in an organic solvent, wherein the organic solvent is selected from 2-methyltetrahydrofuran, tetrahydrofuran, dihydrogen sulfoxide, Alkane and any mixture thereof, the water content in the solution is 2% to 7% by weight of the total solution, as measured by Karl Fischer method;

[0348] (ii) optionally, filtering;

[0349] (iii) cooling the resulting solution to a temperature of -5°C to 10°C;

[0350] (iv) optionally, seeding;

[0351] (v) adding an antisolvent selected from C5 to C7 linear or branched alkanes, cycloalkanes, substituted cycloalkanes, toluene, symmetrical ethers and asymmetrical ethers, characterized in that the temperature of the mixture is maintained at -5°C to 10°C during the addition;

[0352] (vi) optionally, adding a further portion of the antisolvent used in step (v) to completely precipitate the solid;

[0353] (vii) recovering the resulting solid and, optionally, drying it.

[0354] Item 8. The method according to Item 7, wherein the concentration of darolamide in the solution of step (i) is generally 160 g / L to 60 g / L, preferably 145 g / L to 135 g / L.

[0355] Clause 9. The process according to clause 7 or 8, wherein step (i) is carried out in 2-methyltetrahydrofuran at a temperature of 25°C to 70°C.

[0356] Clause 10. The method according to any one of clauses 7 to 9, wherein the antisolvent-solvent ratio is from 1:1 to 3:1, preferably 2:1, the ratio being based on the volume of organic solvent present in the solution provided in step (i).

[0357] Clause 11. The process according to any one of clauses 7 to 10, wherein the antisolvent is selected from C5 to C7 linear alkanes, preferably heptane, and toluene, more preferably, the antisolvent is heptane.

[0358] Clause 12. The method according to clause 7, wherein the solution of step (i) is obtained by the steps comprising:

[0359] (viii) providing darolutamide dissolved in a mixture of an organic solvent and water, wherein the organic solvent is selected from 2-methyltetrahydrofuran, tetrahydrofuran, dihydrofuran, Alkanes and any mixtures thereof, wherein the amount of water represents more than 7% by weight of the total mixture, as measured by Karl Fischer;

[0360] (ix) decanting the phases and discarding the aqueous layer;

[0361] (x) distilling the organic solvent at ambient pressure until a residual solution having a darolamide concentration of 160 g / L to 60 g / L is obtained;

[0362] (xi) optionally, adding another portion of a new organic solvent selected from the organic solvent used in step (viii) or a mixture thereof, and performing step (x) to obtain a solution having a water content of 2 to 7 wt % of the total solution, as measured according to Karl Fischer method.

[0363] Item 13. The method according to Item 12, wherein step (viii) is carried out using a solution directly obtained from an organic layer produced by a reaction process leading to obtaining the product darolutamide.

[0364] Item 14. The method according to Item 13, wherein the reaction is a reduction process of darotamidone (II) carried out in the presence of sodium borohydride as a reducing agent in a mixture of an organic solvent and water, wherein the organic solvent is selected from 2-methyltetrahydrofuran, tetrahydrofuran, dihydrogen sulfoxide, Alkanes and mixtures thereof.

[0365] Clause 15. Use of a nanocrystalline form as defined in any one of clauses 1 to 6 in the preparation of a pharmaceutical composition.

[0366] Clause 16. A pharmaceutical composition comprising a nanocrystalline form as defined in any one of clauses 1 to 6 and at least one pharmaceutically acceptable excipient.< / hs> < / he> < / hs> < / hs> < / hs> < / he>

Claims

1. A N-[(2S)-1-[3-(3-chloro-4-cyanophenyl)-1H-pyrazol-1-yl]-propan-2-yl]-5-(1-hydroxyethyl)-1H-pyrazole 2. The nanocrystal form according to claim 1, characterized in that: When the wavelength is 3. The nanocrystal form according to claim 2, characterized in that: When the wavelength is 4. The nanocrystalline form according to any one of the preceding claims, characterized in that The nanocrystal has 5. The nanocrystalline form according to any one of the preceding claims, characterized in that When heated at 10°C / min 6. The nanocrystalline form according to any one of the preceding claims, characterized in that The nanocrystalline form 7. A method for preparing a nanocrystalline form as defined in any one of the preceding claims, the method comprising (i) providing a solution of darolamide in an organic solvent, wherein the organic solvent is selected from 2-methyltetrahydrofuran, tetrahydrofuran (ii) optionally, filtering; (iii) cooling the resulting solution to a temperature of -5°C to 15°C; (iv) optionally, seeding; (v) adding a hydrocarbon selected from C5 to C7 straight or branched alkanes, cycloalkanes, substituted cycloalkanes, toluene, symmetrical ethers and (vi) optionally, adding a further portion of the antisolvent used in step (v) to completely precipitate the solid; (vii) recovering the resulting solid and optionally drying it.

8. The method according to claim 7, wherein: The concentration of darolamide in the solution of step (i) is generally 9. The method according to claim 7 or 8, wherein: The step (i) is carried out at a temperature of 25°C to 70°C.

10. The method according to any one of claims 7 to 9, wherein: The antisolvent-solvent ratio is 1:1 to 3:1, 11. The method according to any one of claims 7 to 10, wherein: The antisolvent is selected from C5 to C7 12. The method according to claim 7, wherein: The solution of step (i) is obtained by comprising the following steps: (viii) providing darolutamide dissolved in a mixture of an organic solvent and water, wherein the organic solvent is selected from 2-methyltetrakis (ix) if two phases are present, decant the phases and discard the aqueous layer; (x) Optionally, distilling the organic solvent at ambient pressure until a darolamide concentration of 160 g / L to 30 g / L is obtained. (xi) optionally, adding another portion of a new organic solvent selected from the organic solvent used in step (viii) or a mixture thereof 13. The method according to claim 12, wherein: Step (viii) is to obtain darolamide by 14. The method according to claim 13, wherein: The reaction is carried out in the presence of sodium borohydride as a reducing agent.

15. Use of a nanocrystalline form as defined in any one of claims 1 to 6 in the preparation of a pharmaceutical composition.

16. A pharmaceutical composition comprising a nanocrystalline form as defined in any one of claims 1 to 6 and